Aplicação de ferro zero valente imobilizado em carvão ativado para o tratamento de água residuária com cromo hexavalente remanescente - Araújo, Gracieli Xavier de (2018)
The heavy metals are not biodegradable and tend to accumulate in living organisms and are also recognized to be toxic or carcinogenic. The use of particles of zero valent iron (ZVI) is reported as an alternative technique with high potential for in situ and ex situ remediation of matrices contaminated with this metal, mainly due to its large active surface area and significant adsorption capacity, to consolidate into a simple and efficient method of treatment. In this study, iron zero-valent (ZVI) particles were synthesized by the chemical reduction method using hydrated ferrous sulfate hepta (FeSO4.7H2O) and sodium borohydride (NaBH4) with subsequent aggregation to activated carbon powder (PAC) particles, forming the adsorbent PAC-ZVI, which was characterized by the techniques of XRD, SEM, FTIR and PCZ, which revealed the integration of the catalyst to the PAC matrix. Afterwards, the effect of pH on the Cr (VI) removal was evaluated and a kinetic adsorption study was performed. An optimized removal condition was observed at pH 3 in 60 minutes interval with 71% chromium removal. Subsequently, developed kinetic studies revealed that the adsorption kinetics was better adapted to a pseudo second order model, the isotherms were better represented by the Freundlich model and the thermodynamic results demonstrated that the adsorption reaction occurred through a spontaneous process, with interaction endotherm between Cr (VI) and PAC-ZVI with increased randomness of the system, through a physical process of adsorption. Finally the PAC-FVZ adsorbent was applied in the remediation of waste water from the electroplating industry with hexavalent chromium, presenting at pH 3 and 15 minutes interval, 74% Cr (VI) removal. It was also observed that with increasing PAC-FVZ adsorbent concentration the Cr (VI) removal efficiency also increased.